USA‘s Attention as a Source of Ontological Security: Analysis of Lithuanian Values-based Foreign Policy Towards China - Petrošius, Pijus Domantas (Politologija, 2025)
Why did Lithuania, as a small state and in a clearly asymmetric power relationship, decide to pursue a values-based foreign policy towards a great power China? The research suggests that Lithuania’s status as a “good friend of Americans” provides ontological security to decision makers, reinforcing its position in the Western social hierarchy. The research follows the methodological principles of modern constructivist research, utilising discourse analysis and process tracing. The discourse analysis highlights the significance of the status category “good friend of Americans” in the Lithuanian biographical narrative. This is followed by testing a causal mechanism of ontological insecurity constructed from ontological security and social identity theories in the case of 2020–2022. The study contributes to the literature on small states’ behaviour by delving into status-seeking routines to which small states may attach themselves. It also provides new insights into the interaction between small states and great powers.